The Treatment of Oily Wastewater and Septic Tank Effluent by Biofiltration System - Sapari, Nasiman (2011)
Many petrol stations discharge the effluent from their septic tanks and oil traps into storm drains. The treatment system at the station provides only partial treatment of the wastewater, thus additional treatment is required. This study examines the potential of biofiltration system as a further treatment of the effluent for the removal of organic pollutants and nutrients. Four laboratory scale biofiltration columns of 50 cm in length and 12 cm in diameter consisting of sand layer, activated carbon layer and potting mixed soil layer were used in this study. The columns were used for the treatment of combined oily wastewater with treated sewage effluent under unsaturated and saturated conditions. The influent and effluent samples were collected and analyzed for total oil and grease (TOG), chemical oxygen demand (COD), total suspended solids (TSS), turbidity, ammonia, nitrate and total phosphorus. Results from the unsaturated condition indicated COD breakthrough at about 10 pore volumes while oil and grease at about 12 pore volumes. Nitrate reached its breakthrough after 2 pore volumes where ammonia did not show any breakthrough throughout the experiment. The saturated biofiltration removed oil and grease, COD, TSS, turbidity, ammonia, nitrate and phosphorus by 97%, 90%, 70%, 77%, 86% and 85%, respectively. Biofiltration treatment for combined wastewater from petrol stations under saturated condition has better performance than the treatment by unsaturated flow.